2002
DOI: 10.1080/01926230290105785
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Mesonephric Duct (Rete Anlage) Origin for Cysts and Proliferative Epithelial Lesions in the Mouse Ovary

Abstract: Ovaries and adjacent parovarian (mesovarial) tissues of CD-1 mice of various ages were examined to characterize cystic and proliferative epithelial lesions of the ovary and parovarian tissues. Ovaries and adjacent tissues from 6 mice each at approximately 3 and 8 months of age were processed for light microscopy and step-sections (50-l intervals) of the entire tissue were examined. Tissues were collected from 40 mice each at 16 through 24 months of age and 3 step sections per mouse were examined. Mesonephri c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 6 publications
3
33
1
Order By: Relevance
“…Dilation of the rete ovarii with age has been noted previously in CD-1 (Swiss Webster) mice [2,19] and appears to be a feature of this outbred strain, since similar cysts are not found in 12-month virgin or breeder inbred C57/BL6 or 9-month outbred Quackenbush mice (J. S. Fleming, unpublished observations). Recent studies by Clark-Knowles and colleagues showed conditional knockout of the Brca1 gene in the OSE of FVB mice, led to an increase in preneoplastic changes in ovarian biology, including OSE invagination, epithelial cell hyperplasia and small inclusion cysts, but did not give rise to ovarian cancers, up to 8 months after inactivation of Brca1 in the OSE [20].…”
Section: Discussionsupporting
confidence: 72%
“…Dilation of the rete ovarii with age has been noted previously in CD-1 (Swiss Webster) mice [2,19] and appears to be a feature of this outbred strain, since similar cysts are not found in 12-month virgin or breeder inbred C57/BL6 or 9-month outbred Quackenbush mice (J. S. Fleming, unpublished observations). Recent studies by Clark-Knowles and colleagues showed conditional knockout of the Brca1 gene in the OSE of FVB mice, led to an increase in preneoplastic changes in ovarian biology, including OSE invagination, epithelial cell hyperplasia and small inclusion cysts, but did not give rise to ovarian cancers, up to 8 months after inactivation of Brca1 in the OSE [20].…”
Section: Discussionsupporting
confidence: 72%
“…9E, F), consistent with the epithelial origin of these cells. Unlike OSE, which is devoid of cilia, cells of the ovarian rete epithelium expose multiple motile cilia on their apical surfaces (Long, 2002; Tan et al, 2005). Staining for acetylated α-tubulin, a well-known marker of the ciliary axoneme, demonstrated that epithelial cells underlying the ovarian cysts in mutant ovaries expressed cilia on their apical surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While there was an apparent treatment-related increase in paraovarian cysts in CD-1 mice fed BPA compared to the concurrent controls, Tyl et al (2007) indicated that response should be discounted due to the pathogenesis of the particular lesion in aging mice and the incidence in historical controls (Long, 2002). If biologically relevant, this lowest BMDL 10 is 15-fold higher than the 5-mg/kg-d NOAEL based on changes in liver histology associated with chronic BPA ingestion (Tyl et al, 2007).…”
Section: Appendix: Benchmark Dose Evaluation Of Tyl Et Al (2002 2007)mentioning
confidence: 95%